Promoting Research Governance Through Integrity And Ethical Practices: A Qualitative Study - Panigrahi, Shrikant; Mohd Ridzuan, Darun; M., Waris; T., Senthil Kumar (Universiti Malaysia Pahang, 2017)
This paper provide a qualitative analysis on promoting research governance in the higher learning institutions. The purpose of this paper is to analyse importance of research integrity and ethical practices in higher learning institutions qualitatively for the implementation of good governance in research practices. Qualitative research is utilized to discover the deeper associations that underlie individual researcher’s approach for research integrity avoid any misconduct. Comments on qualitative questions asked to university lecturers were coded systematically. The research quantify the qualitative interview data through data query, and cross tabulation. To synthesize the findings, thematic analysis was used which were interpreted within the study context of promoting governance, research integrity and ethical practices. This paper also provide recommendations for additional research and further discussions on these issues. The thematic findings confirmed that researchers need to maintain high standard of research integrity together with appropriate, ethical, legal and obligations ensuring highest standards of rigor to support research integrity.